2022
DOI: 10.1038/s42003-022-03751-9
|View full text |Cite
|
Sign up to set email alerts
|

The chromosome-scale genome sequence of Triadica sebifera provides insight into fatty acids and anthocyanin biosynthesis

Abstract: The Chinese tallow tree (Triadica sebifera) can produce oil with high content of unsaturated fatty acids in seeds and shows attractive leaf color in autumn and winter. Here, the 739 Mb chromosome-scale genome sequence of the Chinese tallow tree was assembled and it reveals the Chinese tallow tree is a tetraploid. Numerous genes related to nutrition assimilation, energy utilization, biosynthesis of secondary metabolites and resistance significantly expanded or are specific to the Chinese tallow tree. These gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…The first peak occurred at approximately 0.38, while the other peak occurred at approximately 0.24 (Figure 2f ). In previous studies, several plants in the spurge family (Euphorbiaceae) and V. vinifera also showed peaks of 4DTv at approximately 0.38, and this peak was regarded as a WGD event in the common ancestor of these plants (Luo et al ., 2022 ). These data also indicated that peaks of 4DTv at approximately 0.38 is not specific to the family of legumes.…”
Section: Resultsmentioning
confidence: 99%
“…The first peak occurred at approximately 0.38, while the other peak occurred at approximately 0.24 (Figure 2f ). In previous studies, several plants in the spurge family (Euphorbiaceae) and V. vinifera also showed peaks of 4DTv at approximately 0.38, and this peak was regarded as a WGD event in the common ancestor of these plants (Luo et al ., 2022 ). These data also indicated that peaks of 4DTv at approximately 0.38 is not specific to the family of legumes.…”
Section: Resultsmentioning
confidence: 99%
“…Genomic variations, including SNPs, indels, and SVs, are also naturally connected in the same long read, making it much easier to phase alleles or haplotypes ( Stander et al., 2021 ). Several polypoid medicinal plants [such as Triadica sebifera (4n=88) ( Luo et al., 2022 ), Rehmannia glutinosa (4n=56) ( Ma et al., 2021 ), Aquilegia oxysepala var. kansuensis (4n=28) ( Xie et al., 2020 )], species with high genome heterozygosity [such as Aloe vera (11.3%) ( Jaiswal et al., 2021 ), Curcuma longa (4.83%) ( Chakraborty et al., 2021 ), Gar.…”
Section: Advantages and Challengesmentioning
confidence: 99%
“…These observations indicate that peonidin-3-O-glucoside and cyanidin-3-xyloside may play pivotal roles in the accumulation of the purple pigment in T. sebifera leaves. Similarly, cyanidin 3-Oglucoside has been confirmed to be the primary colouring substance in red-leaved T. sebifera(Luo et al 2022). These findings thus indicate that the colour of T. sebifera leaves is influenced by the specific types and amounts of anthocyanins present, including peonidin-3-O-glucoside, cyanidin-3-xyloside, and cyanidin 3-Oglucoside.…”
mentioning
confidence: 90%
“…Among these ornamental species is the Chinese tallow tree ( Triadica sebifera ), a plant in the family Euphorbiaceae, which has been cultivated in China for more than 1500 years (Luo et al 2022). It is a multi‐purpose species with diverse uses, including the production of oil, and also has medicinal properties and high ornamental value (Gao et al 2016).…”
Section: Introductionmentioning
confidence: 99%